The effect of macrophages and their exosomes in ischemic heart disease - Wang, Minrui; Li, Chunhong; Liu, Yuchang; Jin, Yuanyuan; Yu, Yang; Tan, Xiaoqiu; Zhang, Chunxiang (Frontiers in Immunology, 2024)
Ischemic heart disease (IHD) is a leading cause of disability and death worldwide, with immune regulation playing a crucial role in its pathogenesis. Various immune cells are involved, and as one of the key immune cells residing in the heart, macrophages play an indispensable role in the inflammatory and reparative processes during cardiac ischemia. Exosomes, extracellular vesicles containing lipids, nucleic acids, proteins, and other bioactive molecules, have emerged as important mediators in the regulatory functions of macrophages and hold promise as a novel therapeutic target for IHD. This review summarizes the regulatory mechanisms of different subsets of macrophages and their secreted exosomes during cardiac ischemia over the past five years. It also discusses the current status of clinical research utilizing macrophages and their exosomes, as well as strategies to enhance their therapeutic efficacy through biotechnology. The aim is to provide valuable insights for the treatment of IHD.